EFFECT OF LIQUID NITROGEN LEVELS DURING STORAGE ON QUALITY OF FROZEN SEMEN OF GIR BULLS - SONAR, B P; TIWARl, R P; MISHRA, G K; POYAM, M R; PANDEY, A K; NAIR, A K; SAHASRABUDDHE, S A (The Indian Journal of Animal Reproduction, 2023)
A total of 50 semen ejaculates collected from 5 Gir bulls were frozen and stored in 3 liter container to study the effect of different levels of liquid nitrogen on various post thaw seminal attributes. Overall mean values of post thaw motility, hypo osmotic swelling reactive sperm and cervical mucus penetration were 54.33 ± 1.18, 52.33 ±1.37, 47.00 ± 1.18, 28.67 ± 1.14%, 55.73 ± 2.08, 53.93 ± 1.70, 48.93 ± 2.18, 38.07 ± 1.79%, and 29.13 ± 0.96, 28.33 ± 0.83, 26.53 ± 1.06 and 19.87 ± 0. 72 mm while liquid nitrogen level was full, 314th, half and 114th of frozen semen straw, respectively. The overall percent post thaw motility, percent HOS positive sperm and the mean distance traveled by vanguard spermatozoa (CMPT) was found significantly lower (P<0.01) when the level of liquid nitrogen remained 114th level of straws as compared to full, 314th , and 1/2 levels. Overall mean values for post thaw motility, hypo osmotic swelling test and cervical mucus penetration test were best observed during the full level of liquid nitrogen and dropped significantly when level of liquid nitrogen reached to 114th level of semen straws in 3 liter LN2 container.